Evaluasi Pertumbuhan Klon Tanaman Tebu (Saccharum officinarum L.) Ratoon I Di Desa Watesari, Kecamatan Balongbendo, Kabupaten Sidoarjo - Mochammad Jamaludin Husain; Setyo Budi; Suhaili (GEMA AGRO, 2023)
In the last five years, sugar cane production in Indonesia has fallen by 4%. Sugar self-sufficiency can be achieved through plant breeding programs to create high-yielding sugarcane varieties. The research objective was to determine the correlation between growth variables, genetic diversity, and sugarcane (Saccharum officinarum L.) growth in test clones. The research was conducted at the Watesari Village, Balongbendo District, Sidoarjo Regency in November 2022 - August 2023. The test materials were clones SB01 UMG NX 22, SB03 UMG NX 22, SB04 UMG NX 22, SB11 UMG NX 22, SB12 UMG NX 22, SB19 UMG NX 22, and SB20 UMG NX 22, BL variety and PS881 variety. The variables observed included stem height, stem diameter, number of stems, number of leaves, and brix. Data analysis used ANOVA, DMRT test, correlation test, genetic diversity, and heritability. The SB12 UMG NX 22 clone had the best growth, including stem height of 293.89 cm (39 MSK); total of 8.22 units (31 MSK), 8.44 units (33 MSK), 8.44 units (35 MSK), 8.78 units (37 MSK), and 9.11 units (39 MSK). There is a correlation between growth variables. There are genetic variations that affect the growth of sugarcane plants including moderate KKG values ​​(stem diameter, number of stems, and brix). Low KKG (stem height and number of leaves). Low GFC (stem height, stem diameter, stem, number of leaves and brix). H2 height (rod height, stem diameter, number of rods, and brix). Moderate H2 (number of leaves).